Global gatekeeping, representation, and network structure: a longitudinal analysis of regional and global knowledge-diffusion networks - Spencer, J W (Journal of International Business Studies, 2003)
This paper argues that structural characteristics of knowledge-diffusion networks, such as density levels, centralization levels, and the presence of global knowledge brokers, contribute to the emergence of dominant designs and the competitiveness of countries' firms and industries. It further suggests that national institutional structures and firm-specific attributes influence the development of these knowledge-diffusion networks. Six propositions, developed from examination of one industry's networks and previous scholarly literature, specify these arguments.